Dampak dan Strategi Kebijakan Pengembangan Pembiayaan Dan Inklusifitas Keuangan Dalam Peningkatan Pembiayaan Bank Syariah Di Indonesia - Asiyah, Binti Nur (BISNIS, 2017)
This paper is motivated by the policy of the Financial Services Authority, in which Shariah Banking is able to compete and perform the intermediation function equally and felt by the people of Indonesia. The policy of the Financial Services Authority has a synergy between sharia banking and the Community in the form of easily accessible financing. This paper aims to determine the impact and strategy of development policy of Financing and financial inclusiveness in increasing the financing of Bank Syariah in Indonesia. The method used is qualitative approach, descriptive type. The result of this paper is the policy of development of financing and financial inclusions have a significant impact for the improvement of financing. The strategies for the policy to produce maximum financing; first the need for support from the government as regulatory publishers, universities, state enterprises to support the financing climate; secondly, the shift of regulatory thinking from the achievement of the quantity of funds alone, but also must be based on the number of people who can be served. Third Improvement of Sharia Banking Human Resources with the training policy, providing sufficient incentives and minimum standards for recruitment of sharia banking managers. Thirdly, sharia banking always considers Third Party Funds Management, Fourth; consider the profit-sharing rate used in the financing contract. Fifth, Sharia Banks have the opportunity to cooperate (chanelling) with Non-Governmental Groups that have been free from poverty, and maximize financing for the allocation of Micro Small and Medium Enterprises.